Implementation of Montessori Method in Developing Freedom and Independence Values at TKS Islam YPAA Sumenep - Danang Prastyo; Gunarti Dwi Lestari; Heryanto Susilo; Ardhana Reswari; Selfi Lailiyatul Iftitah (Institut Agama Islam Negeri Madura, 2025)
This study aims to explore the application of the Montessori method in implementing values of freedom and independence in early childhood at TKS Islam YPAA Pangarangan Sumenep. The Montessori method was chosen because it is considered capable of accommodating children's learning needs personally, by providing directed freedom and an environment that supports independent exploration. This research uses a qualitative approach with observation and interviews as data collection techniques. The informants in this study consisted of the principal, classroom teachers, and students. The results indicate that the value of freedom is reflected in various activities such as collage, counting, and shape-building, which allow children to choose media and tools based on their interests. Children's independence is developed through practical activities such as wearing socks and washing vegetables. The teacher acts as a facilitator who supports exploration without reducing the children's freedom. The application of shaping techniques has also proven effective in developing independent skills. In conclusion, the Montessori method at TKS Islam YPAA Pangarangan Sumenep successfully supports the development of freedom and independence in children, in line with the principles formulated by Maria Montessori, although there are several supporting and inhibiting factors in its implementation.